PENGARUH UTANG PERUSAHAAN TERHADAP KINERJA KEUANGAN - Abid Ramadhan (LPPM STIE Muhammadiah Bandung, 2019)
Debt is an economic sacrifice that must be made by the company in the future caused because of previous actions and transactions. Debts are classified into two, namely the short-term debts and Long Term Debt. Short-term debt has a maturity of less than one year whereas long-term debt of more than one year. This research use the ROE (Return On Equity) because it can indicate the success or failure of the company's management company maximise the level of shareholder return on investment results. The purpose of this study was to examine the influence of corporate debt in the form of Short Term Debt (STD), Long Term Debt (LTD) and the Total Debt (TD) as variables are independent of financial performance in the form of Return On Equity as the dependent variable. The population in this study are companies listed on the Jakarta Islamic Index (JII) in 2015-2017. Engineering data collection using a purposive sampling method. The data were analyzed by using multiple linear regression. The results of this study indicate that the Short Term Debt (STD), Long Term Debt (LTD) and the Total Debt (TD) effect on Return On Equity (ROE).